Low Vitamin B12 in Patients on Admission to an Amputation Rehabilitation Unit: A Retrospective Study. (12th September 2014) - Earl, Eric; Wong, Renee; Payne, Michael W. C.
Abstract : Objective: The purpose of this study was to determine the prevalence of low vitamin B12 (VB12) in patients on admission to an amputation rehabilitation unit and identify specific populations at risk. Methods : A retrospective chart review was performed for 127 participants comprising patients with major lower limb amputations admitted to a regional amputation rehabilitation program between January 1, 2011 and December 31, 2012. Electronic medical records were reviewed for demographic data, amputation data, medication history, serum VB12 levels, and other related blood work. A literature‐based cutoff of VB12 <260 pmol/L was used as the criterion for low VB12. Results : The prevalence of low VB12 was 59.8%. Patients aged ≥55 years were found to have an increased prevalence of low VB12 ( P = .05). Serum VB12 levels were significantly lower among patients aged ≥55 years ( P < .05) and among patients with a mean corpuscular volume >97 fL ( P < .01). No other differences in prevalence were determined among different demographics, etiologies, or comorbidities. Conclusions : Patients with an amputation have a high prevalence of low VB12 levels compared with the general population. Low VB12 status may impact rehabilitation outcomes through anemia, cognitive decline, and neuropathy. No reliable indicators for which patients should be screened were found, and therefore, a universal approach to screening and treatment is needed.